Bystander CD8+ conventional memory versus virtual memory T cells in the initial days post-Trypanosoma cruzi infection - Viano, Maria Estefania; Baigorri, Ruth Eliana; Bergero, Gastón; Aoki, Maria Pilar; Lidon, Nicolas Leonel; Teixeira, Maria Guadalupe; Herrera, Melisa Rocio; Motran, Claudia Cristina; Cerban, Fabio Marcelo; Stempin, Cinthia Carolina; Rodriguez-Galan, Maria Cecilia (Frontiers in Immunology, 2025)
BackgroundBystander activation has primarily focused on conventional antigen-specific T cells (TMEM) and other innate immune cell types. However, the role of virtual memory T cells (TVM) has been largely overlooked, despite their numerical superiority and highly cytotoxic phenotype. Bystander activation is particularly relevant in infections caused by intracellular pathogens. In this study, we aimed to compare the bystander activation potential of TVM cells versus TMEM cells during the early days following T. cruzi infection.Methodology/Principal FindingsOur results demonstrate that TVM and TMEM cells, evaluated by flow cytometry, are present but do not undergo significant changes in frequency during the first four days post-infection (p.i.). In an in vitro co-culture system, TVM or TMEM cells pre-incubated with IL-12 and IL-18 (effector cells) were cultured with T. cruzi-infected enriched peritoneal macrophages (Tc-PM, target cells). Immunofluorescence assays revealed that both TVM and TMEM cells exhibit a highly efficient capacity to kill the parasite and induce degranulation, in contrast to naïve T cells (TN), which showed almost no cytotoxic activity. Furthermore, intracellular flow cytometry assays confirmed that both TVM and TMEM cells produce substantial amounts of IFNγ up to 4 days p.i. when stimulated in vitro with IL-12 and IL-18, whereas TN cells fail to produce this cytokine. Accordingly, TVM and TMEM cells exert their cytotoxic effects via IFNγ production, rather than NKG2D, which subsequently activates reactive oxygen species (ROS) and Nitric Oxide (NO) pathways in Tc-PM. Additionally, we demonstrate that in TVM cells, IFNγ signaling occurs through STAT1 in Tc-PM. Finally, analysis of human TVM cells within PBMCs, revealed increased expression of the functional marker granzymes in Chagas disease patients compared to healthy controls.Conclusions/SignificanceThese results challenge the view that only TMEM cells dominate early infection control. The equivalency of TVM and TMEM cells in parasite clearance suggests TVM cells are valuable innate-like contributors, providing rapid protection. Their numerical prevalence in unprimed individuals indicates TVM cells may be an underestimated component of early immunity.